THE REVOLUTION IN MILITARY AFFAIRS AND SUSTAINABLE DEVELOPMENT - Teodor FRUNZETI (Annals: Series on Military Sciences, 2013)
Associating war with the idea of destruction made it to be considered completely incompatible with the concept of sustainable development. However, the military innovations (technologies, operational concepts, organizational adaptation) can be regarded as vectors not only of destruction, but also of evolution. This paper addresses the relationship between the concepts of Revolution in Military Affairs and sustainable development, the emphasis being placed on the content and dynamics in the contemporary period, marked by major changes in the socio-economic of changes that include the dramatic development of telecommunications, computers and technology.